2010
DOI: 10.12693/aphyspola.118.1143
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Free Space Optical Detection Module Operating at the Wavelength Range of 8-12 μm

Abstract: The paper presents the construction and test results of a long-term radiation detector module for free space optical communication operated at the wavelength range of 8-12 µm. In the module a Polish detector manufactured in the company Vigo System S.A. was applied. High sensitivity of the detection module was achieved through a multi-layered heterostructure HgCdTe with immersion lens, which is optimized for the radiation detection at the wavelength of 10 µm. Detector noises were reduced as a result of detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These links are also safe for eyesight [21]. The conducted analyses show that for the construction of an optical link in open space, characterized by lower attenuation in hazy conditions than currently existing ones, QC lasers and MCT photodiode operating in the spectral range of 8-12 µ m can be used [22][23][24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These links are also safe for eyesight [21]. The conducted analyses show that for the construction of an optical link in open space, characterized by lower attenuation in hazy conditions than currently existing ones, QC lasers and MCT photodiode operating in the spectral range of 8-12 µ m can be used [22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 presents the most important parameters of this module, optimized for a wavelength of 10 µm. More detailed descriptions and experimental research on detection modules, shown in Figure 2, are presented in References [23,24]. In the transmitter module, a cascade laser from Alpes Lasers was used [34].…”
Section: Methodsmentioning
confidence: 99%
“…The research of laser pulse shape was carried out using the QC laser driver system, detection module produced by Vigo S.A PVI series [19][20][21][22][23] and oscilloscope Tektronix series 4000. In Fig.…”
Section: Investigation Of Laser Pulse Shapementioning
confidence: 99%